Why is Dental Public Health residency program needed in Pakistan? - Farhan Raza Khan (KARACHI MEDICAL AND DENTAL COLLEGE, 2023)
Community dentistry or dental public health residency program are non-existent in Pakistan. Due to this, the dental institutions find it extremely difficult to hire and retain teachers in this discipline. There are other subjects such as Special Care Dentistry and Oral Medicine which too are lacking in our country. However, these disciplines are locally overseen by faculty of Oral Maxillofacial Surgery. Interestingly, other emerging disciplines such as Dental Anesthesiology, Oral Radiology and Oral Pathology are standalone specialties recognized by the American Dental Association but in Pakistan, these subjects fall in the domain of medical specialties of anesthesiology, radiology, and pathology, respectively. The two dental disciplines that warrant immediate attention of the dental academia and should be established as subject specialties are: Dental Public Health (DPH) and Pediatric Dentistry. This short communication discusses the significance and methodology of initiating a residency (fellowship training) program in Dental Public Health.